Biomass-derived mesopore-dominant porous carbons with large specific surface area and high defect density as high performance electrode materials for Li-ion batteries and supercapacitors. (June 2017) - Niu, Jin; Shao, Rong; Liang, Jingjing; Dou, Meiling; Li, Zhilin; Huang, Yaqin; Wang, Feng
Abstract: Porous carbons with high specific surface area and high defect density have been prepared through direct carbonization of cattle bones without any additional activators and templates. Benefiting from self-activation induced by hydroxyapatites within the cattle bones, the high-defect porous carbons obtained at 1100 °C (PC-1100) possess the high specific surface area (2096 m 2 g −1 ), largest mesopore volume (1.829 cm 3 g −1 ), a narrow mesopore size distribution centered at approximately 4.0 nm and good electrical conductivity (5141 S m −1 ). Due to the synergistic effect of the defects and pores, PC-1100 as the anode for Li-ion battery exhibits a high reversible capacity of 1488 mA h g −1 after 250 cycles at 1 A g −1 and 661 mA h g −1 after 1500 cycles at 10 A g −1 . Even at 30 A g −1, PC-1100 can still deliver a high reversible capacity of 281 mA h g −1, showing superior lithium storage capability. Moreover, the symmetric supercapacitor based on the PC-1100 in neat EMIM-BF4 electrolyte delivers a high energy density of 109.9 W h kg −1 at a power density of 4.4 kW kg −1, and maintains an energy density of 65.0 W h kg −1 even at an ultrahigh power density of 81.5 kW kg −1, as well as a superior cycling performance (96.4% of the capacitance retention after 5000 cycles). Graphical abstract: High-defect mesopore-dominant porous carbons with large specific surface area have been prepared via direct carbonization of cattle bones, and showed outstanding rate capability and superior cycling performance as electrode materials for Li-ion batteries and supercapacitors. Highlights: Porous carbons were prepared by direct carbonization of cattle bones. Mesopore-dominant carbon with a narrow PSD ( 4 nm) was obtained at 1100 °C. The porous carbon possessed high defect density and good electrical conductivity. The porous carbon showed high performance as electrodes for LIBs and SCs.